2008
DOI: 10.1111/j.1365-2133.2008.08540.x
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency electromagnetic field enhances human keratinocyte cell growth and decreases proinflammatory chemokine production

Abstract: Our results show that ELF-EMF modulates chemokine production and keratinocyte growth through inhibition of the NF-kappaB signalling pathway and thus may inhibit inflammatory processes. ELF-EMF could represent an additional therapeutic approach in the treatment of skin injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
4
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 31 publications
2
86
4
2
Order By: Relevance
“…Reale et al, 2006] or HL-60 myeloid leukemia cells [Tokalov and Gutzeit, 2004]. Changes in the gene expression of pro-inflammatory genes were also found in skin cells [Vianale et al, 2008]. In these studies, the experimental setup and exposure conditions differed strongly from our study, but all studies used a 50 Hz signal.…”
Section: Discussioncontrasting
confidence: 43%
“…Reale et al, 2006] or HL-60 myeloid leukemia cells [Tokalov and Gutzeit, 2004]. Changes in the gene expression of pro-inflammatory genes were also found in skin cells [Vianale et al, 2008]. In these studies, the experimental setup and exposure conditions differed strongly from our study, but all studies used a 50 Hz signal.…”
Section: Discussioncontrasting
confidence: 43%
“…Some of these conflicting data might be due to differences in frequency, intensity, duration and also certain type of cell lines. 17 Generally, despite profound studies, there has not been any accepted molecular mechanism to explain the carcinogenic effects of ELF-EMF. 18 Proteomics is a powerful tool to elucidate underlying mechanism of exposed cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other in vitro studies suggested that ELF-EMF could change the expression of some proteins, which are involved in control of cell proliferation (8,19) while others demonstrate that exposure to ELF-EMF has no effects on cell proliferation, DNA replication, and regulation (20) result of these studies varied with different or opposite effects. Some of these conflicting data might be due to differences in frequency, intensity, duration, and also certain types of cell lines (21). Generally, despite of profound studies, there have not been any accepted molecular mechanisms that explain carcinogenic effects of ELF-EMF (22).…”
Section: Introductionmentioning
confidence: 99%